The Effect of Financial Literacy on Financial Inclusion in Sustaining Indonesia SMEs Growth - Kurniasari, Florentina (Indonesian Journal of Sustainability Accounting and Management, 2023)
As stated in UN Sustainable Development Goals (SDGs), financial inclusion is one strategy to reduce poverty in one country, including Indonesia. The Indonesian government was facing a problem in experiencing a relatively low financial inclusion index. Many Indonesians are reluctant to have business with the financial institution. Increasing the financial literacy rate among Indonesians was expected to get a higher financial inclusion index. Therefore, the main objective of this research was to analyze the effect of financial literacy with all its dimensions included: knowledge, skill, attitude, and behavior on financial inclusion. The Indonesian government had a serious commitment to accelerating economic growth by supporting the role of SMEs as the backbone of the country’s economic development. In fact, many SMEs had some difficulties in getting access to formal financial institutions to support their business growth. As quantitative research, the study distributed questionnaires to 150 SMEs in culinary businesses located in South Tangerang. All data were statistically analyzed. The data collection was further processed statistically using the Structural Equation Method (SEM). The study showed that all variables of financial literacy, including knowledge, skill, attitude, and behavior had a significant effect on financial inclusion. Knowledge had the highest effect on financial inclusion. Therefore, it was an urgency to educate people and provide necessary information related to the financial products and services.